ANALISIS TINGKAT IMPLMENTASI SMK3 PADA KONSTRUKSI BANGUNAN DI SURABAYA BERDASARKAN PP NO 50 TAHUN 2012 - Siti Choiriyah; Feri Harianto; Dian Henggar (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2020)
The development of construction project brings positive effects to the manpower absorption and development equalization. Unfortunately, construction activity also has risks such as a high occupational accident. This research aimed at describing the success level for implementing SMK3 (Sistem Managemen Keselamatan dan Kesehatan Kerja or Occupational Health and Safety Management System at the building construction in Surabaya, particularly at the buildings of Super Mall Pakuwon and Telkom Group Surabaya based on PP No. 50 in 2012. The success percentage of SMK3 was determined by the qualitative method using data analyses through a checklist and interview. Both projects of Super Mall Pakuwon Surabaya and Telkom Group Surabaya were in the satisfactory category by 90.18% and 98.26% respectively. Moreover, the results of the triangulation method indicated that the three themes and sub-themes of both projects concluded the importance of occupational safety and the effectiveness of K3 protection which is planned, measurable, structured, and integrated.